Individual differences in working memory during reading with and without parafoveal information: A moving-window study. - Osaka, Naoyuki; Osaka, Mariko (American Journal of Psychology)
We examined individual differences in working memory appearing in the effective visual field size while reading Japanese text. Working memory capacity was measured by a Japanese reading span test, and the subjects were divided into high- and low-score groups. Reading performance was measured by reading time, comprehension, and eye movements using a variable moving window through which the subject could read areas of the Japanese text. As the window size decreased, the reading time increased significantly. High-span subjects showed better performance in reading time, comprehension, and fixation duration than low-span subjects even in small visual fields. Interestingly, high-span subjects appear to show better information integration during reading, whereas low-span subjects showed less integration without parafoveal vision. These findings suggest that reading performance was better for subjects with larger working memory resources in a parafoveal restriction condition. Reprinted by permission of the publisher.